AN OVERTRAINING SYNDROME AS FUNCTIONAL CARDIOVASCULAR DISORDER DUE TO PHYSICAL OVERLOAD - V. A. Badtieva; V. I. Pavlov; A. S. Sharykin; М. N. Khokhlova; A. V. Pachina; V. D. Vybornov (Российский кардиологический журнал)
In the article, an analysis provided of recent views on the overtraining syndrome by the data from local and foreign publications.The witness of the problem actuality is also an existence of controversial opinions and absence of clear definitions on properties of the condition. It has been revealed that the main role in pathogenesis of the overtraining syndrome do play the changes of cardiovascular, endocrine and central nervous systems. These changes are complicated and ambiguous, depend upon multiple factors, as the type of sport, specifics of exertion and loads, stage of pathophysiological process. Entraining effect of exertion, if incorrectly utilized, underestimation of current condition of a sportsman, might not lead to expected results. Moreover, non-rational application of exertion might lead to opposite effect, that is, to decrease adaptation potential and reserves, towards the edge of the condition as an overtraining syndrome, which shows phasic, progressing character, starting from fatigue and mild disorders, to persistent, rigidly reversible processes.Due to controversy, multiple stages and multifactorial of the overtraining syndrome, by now there is no unified approach to its definition, as no unified standards to its diagnostics, treatment and prevention.